Surgical Infections - GANIYEVA SHAHLO FAYZILLOYEVNA; MANSUROVA GULNOZA MUYINJONOVNA (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
As for all surgical procedures, infection is an important complication. Surgical site infection with intrathecal device placement may present as meningitis, epidural or subdural abscess, and/or encephalitis. The preventive measurements such as showering with chlorhexidine soap, staphylococcal colonization detection and decolonization, and for patients at risk, a preoperative consultation with an infectious disease specialist may be necessary.